ANALYSIS OF ACCOUNTING IMPLEMENTATION IN MSMEs IN BOGOR REGENCY - Nasution, Yan Noviar; Herman, Herman (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This research aims to determine whether the application of accounting in MSMEs in Bogor Regency is in accordance with SAK EMKM. This research uses a qualitative method with a case study approach. The data used in this research is primary data obtained through observation and interviews as well as documentation data and secondary data sourced from MSMEs owners in Bogor Regency. The results of the research show that the application of accounting in MSMEs is not in accordance with the application of SAK EMKM because the preparation of financial reports in MSME companies has not been implemented fully or has not been optimal, as can be seen in the table of application of MSMEs Accounting where the CALK section is not in accordance with the SAK EMKM method.